Electoral geography and manifestoes of new «urban» parties from 1977 to 1999: how urban are they really? - Filip De Maesschalck; Maarten Loopmans (Belgeo)
This paper examines the relationship between electoral results and party manifestoes from a spatial perspective. The manifestoes and electoral geography of two new, allegedly «urban» parties in Flanders are compared in order to assess whether these parties might, in their ideas and consequential policies, contribute to a reinforcement of the urban milieu in Flanders. We end up with a rather pessimistic conclusion: the Vlaams Blok, adhering an inherently anti-urban ideology, nor Agalev, who have to satisfy a suburban as well as an urban electorate, seem to be able to defend the urban milieu in Flanders.